2014
DOI: 10.5959/eimj.v6i2.235
|View full text |Cite
|
Sign up to set email alerts
|

Approach to learning of medical students in a Caribbean medical school

Abstract: Introduction: Students' perception of the learning environment, the curriculum and assessment may influence their approach to learning. Student approach to learning has not been previously studied at Xavier University School of Medicine, Aruba. Hence the present study was carried out. Objective: Obtain information about respondents' conceptions of learning, approaches to studying and preferences for different types of courses and teaching Method: The Approaches and study skills inventory (ASSIST) was administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 1 publication
2
10
0
Order By: Relevance
“…To date, limited studies were conducted to investigate the effect of learning styles on the educational performance of medical science students in the Caribbean region. A study was conducted in the Xavier University School of Medicine, Aruba using the ASSIST questionnaire and found that students mainly used deep and strategic learning, which is also consistent with findings (36). Another study conducted in the Faculty of Medical Sciences at the University of the West Indies (UWI) St. Augustine campus using the ASSIST questionnaire to examine the motivational factors and approaches to learning of medical students identified that motivation to study was significantly and positively associated with deep and strategic approaches to learning and negatively associated with and surface approach to learning (37 (38).…”
Section: Discussionsupporting
confidence: 71%
“…To date, limited studies were conducted to investigate the effect of learning styles on the educational performance of medical science students in the Caribbean region. A study was conducted in the Xavier University School of Medicine, Aruba using the ASSIST questionnaire and found that students mainly used deep and strategic learning, which is also consistent with findings (36). Another study conducted in the Faculty of Medical Sciences at the University of the West Indies (UWI) St. Augustine campus using the ASSIST questionnaire to examine the motivational factors and approaches to learning of medical students identified that motivation to study was significantly and positively associated with deep and strategic approaches to learning and negatively associated with and surface approach to learning (37 (38).…”
Section: Discussionsupporting
confidence: 71%
“…The study findings have commonalities with other peer-reviewed work carried out among comparable populations of medical students, which have also displayed a predominant deep approach to learning (12,7). However, there are some intricate details past questions, unchanged.…”
Section: Approachessupporting
confidence: 72%
“…The strategic approach to learning identifies that group of learners who set decisive learning goals at the outset, develop and adhere to a plan to accomplish these goals (7). It is a deliberate decision borne out of intrinsic motivation.…”
Section: Study Setting and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend raises questions about how learners perceive the disciplines of medicine and dentistry. Shankar et al 42 . have shown that students who adopt a DAL tend to view learning as individual development.…”
Section: Discussionmentioning
confidence: 99%